PERGESERAN IDENTITAS BUDAYA DALAM NASKAH LAKON PUTU WIJAYA BILA MALAM BERTAMBAH MALAM: KAJIAN POSTMODERNISME - Prihantono, Kahar (ALAYASASTRA, 2018)
This study attempted to reveal cultural identity shifts in the Putu Wijaya?s play script Bila Malam Bertambah Malam (BMBM) observed from Jean Francois Lyotard?s postmodernism point of view. This study employed sociology in literature approach to analyze the cultural identity of the characters in the BMBM play script, next it would be connected with any symptoms of the Jean Francis Lyotard postmodernism. The results of the study proved that there were cultural identity shifts in the BMBM play script in term of postmodernism point of views including the liberation, reformation, and identity deception and falsify (as an impression formation). The character of Gusti Biang possessed arrogant characteristics to her lowest class assistant (Wayan) in fact the assistant was the biological father of her son. She despised his assistants (Wayan and Nyoman), and opposed to the his son?s (Ngurah) romance with Nyoman. The identity deception as the impression formation appeared in Gusti Biang?s arrogant attitude, she kept glorifying her upper class status (satria) and insulting lowest class status (sudra) although Wayan was the person she loved after the death of her impotent husband. The symptoms of liberation and reformation in term of social class was captured in loyal servant character, Wayan. He devoted himself to his love, Gusti Biang, although the old tradition prohibited him to marry Gusti Biang. Later, both Ngurah and Nyoman dared themselves to break the tradition of inter-class romance.Keywords: cultural identity; social class; postmodernism; sociology in literature; interclass romance;